Aty-baty . Aty-baty . One, Two . Аты-баты - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Losses of the Russian army in international conflicts; accusation of the Russian servicemen, dislocated in Estonia, of trade of radioactive materials; the conflict in Nagorno-Karabakh; destiny of a military pilot Dmitrii Petrov who survived in air crash in the Congo jungles. Потери российской армии в международных конфликтах; обвинение российских военнослужащих, дислоцированных в Эстонии, в торговле радиоактивными веществами; конфликт в нагорном Карабахе; судьба военного летчика Дмитрия Петрова, выжившего после авиационной аварии в джунглях Конго.